Study of Sea Water Quality in Malalayang Beach Walk Area - Windarto, Firhansyah C.; Rumampuk, Natalie D.C.; Mamuaja, Jane M.; Rampengan, Royke M.; Schaduw, Joshian N. W.; Manengkey , Hermanto W.K. (Sam Ratulangi University, 2024)
The city of Manado is famous for its fishery products, but human activities also cause problems of seawater pollution and a decrease in water quality. This study aims to examine the water quality around Malalayang Beach Walk in Manado City with a focus on physical and chemical parameters. The study was conducted at five stations with three repetitions at high and low tide. The results showed that the water temperature was relatively homogeneous, with a range of 30.02-30.29oC at high tide and 30.39-30.81oC at low tide. Turbidity is in the range of 20.1-22.5 NTU at high tide and 16.0-21.7 NTU at low tide, exceeding the quality standard. DO values conform to quality standards (5.46-8.07 mg/L at high tide and 5.69-6.32 mg/L at low tide), but TDS reaches 23900-28600 mg. L at high tide and 26600-28600 mg/L at low tide, far from the common values of 1500 mg/L. Salinity values range from 25.02-30.29 ppt at high tide and 30.35-30.50 ppt at low tide. Pollution and degradation need to be better controlled and monitored. Keywords: Water quality, Temperature, Turbidity, Dissolved oxygen (DO), Total dissolved solids (TDS), Salinity. Abstrak Kota Manado terkenal dengan hasil perikanannya, namun aktivitas manusia juga menyebabkan masalah pencemaran air laut dan penurunan kualitas perairan. Penelitian ini bertujuan untuk mengkaji kualitas perairan di sekitar Malalayang Beach Walk Kota Manado dengan fokus pada parameter fisika dan kimia. Penelitian dilakukan di lima stasiun dengan tiga kali pengulangan pada saat air pasang dan surut. Hasil penelitian menunjukkan bahwa suhu perairan relatif homogen, dengan rentang nilai 30,02-30,29oC saat pasang dan 30,39-30,81oC saat surut Kekeruhan berada pada rentang 20,1-22,5 NTU saat pasang dan 16,0-21,7 NTU saat surut, melebihi standar baku mutu. Nilai DO sesuai dengan standar baku mutu (5,46-8,07 mg/L saat pasang dan 5,69-6,32 mg/L saat surut), namun TDS mencapai 23900-28600 mg/L saat pasang dan 26600-28600 mg/L saat surut, jauh dari nilai umum 1500 mg/L. Nilai salinitas berkisar antara 25,02-30,29 ppt saat pasang dan 30,35-30,50 ppt saat surut. Pencemaran dan penurunan kualitas perlu dikendalikan dan dipantau secara lebih baik. Kata Kunci: Kualitas air, Suhu, Kekeruhan, Dissolved oxygen (DO), Total dissolved solids